2015
DOI: 10.1039/c4ra15755a
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective preparation and sensing application of conducting polymer PEDOT/ionic liquid nanocomposite with excellent electrochemical properties

Abstract: A stable and porous nanocomposite of PEDOT/IL with excellent electrocatalytic activity was prepared through a cost-effective electrochemical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…PEDOT conducting polymers could be polymerized with ILs to combine the unique properties of conducting polymers with ILs, and also to improve performance and lifetime of PEDOT. Recently, Luo et al . have introduced a cost‐effective electrodeposition method based on a composite of poly (3,4‐ethylenedioxythiophene) doped with pure insoluble IL (1‐ethyl‐3‐methylimidazolium bis (trifluoromethylsulfonyl) imide).…”
Section: Conducing Polymer Nanocomposites‐based Non‐enzymatic Electrodesmentioning
confidence: 99%
“…PEDOT conducting polymers could be polymerized with ILs to combine the unique properties of conducting polymers with ILs, and also to improve performance and lifetime of PEDOT. Recently, Luo et al . have introduced a cost‐effective electrodeposition method based on a composite of poly (3,4‐ethylenedioxythiophene) doped with pure insoluble IL (1‐ethyl‐3‐methylimidazolium bis (trifluoromethylsulfonyl) imide).…”
Section: Conducing Polymer Nanocomposites‐based Non‐enzymatic Electrodesmentioning
confidence: 99%
“…The development of composites modified electrode based on conducting polymer and ionic liquid was investigated by many groups to determinate several molecules, these electrodes combined the excellent properties of both materials . However, there are very limited works regarding the carbaryl determination using the conducting polymer and ionic liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymer-modified electrodes have been widely used for the electrochemical determination of biomolecules [37,38]. Ionic liquid has been used as a substitute for organic solvent for the preparation of gel-like materials [39].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid has been used as a substitute for organic solvent for the preparation of gel-like materials [39]. Reports have shown that the combination of ionic liquids and carbon materials can improve electrode surface fouling problems during the electrochemical detection of certain biomolecules [40,41]; however, there are very limited reports concerning the use of conducting polymer-ionic liquid composites for analytical purposes [38,39], and the composites have not yet been reported for BPA sensing.…”
Section: Introductionmentioning
confidence: 99%